1996
DOI: 10.1016/0167-4889(95)00194-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP stimulates protein synthesis in L6 myoblasts and its effects are additive to those of insulin, vasopressin and 12-0-tetradecanoylphorbol-13-acetate. Possible involvement of mitogen activated protein kinase

Abstract: The role of cyclic AMP as a second messenger in the stimulation of protein synthesis and the potential involvement of mitogen activated protein (MAP) kinase in this response was studied in L6 myoblasts. Dibutyryl-cAMP (dbt-cAMP) increased protein synthesis at 90 min and 6 h in a concentration-dependent manner. The responses at 90 min were probably mediated by increased translation as they were not blocked by actinomycin D; effects at 6 h were accompanied by increases in RNA content implying a transcriptional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…We (13) and others (61) reported that insulin stimulates protein synthesis in L6 myoblasts. In addition, insulin enhances the activity of eIF2B in both skeletal muscle (62,63) and CHO cells overexpressing the human insulin receptor (CHO.IR or CHO.T cells) (64).…”
Section: Discussionmentioning
confidence: 99%
“…We (13) and others (61) reported that insulin stimulates protein synthesis in L6 myoblasts. In addition, insulin enhances the activity of eIF2B in both skeletal muscle (62,63) and CHO cells overexpressing the human insulin receptor (CHO.IR or CHO.T cells) (64).…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, we have previously shown that vasopressin stimulates mitogen-activated protein kinase in these cells (64) and mitogenactivated protein kinase is known to phosphorylate and activate cytosolic PLA 2 (65), releasing arachidonic acid. Thus, it is possible that vasopressin may, at least in part, stimulate protein synthesis in L6 cells through PKC-via mitogen-activated protein kinase, cytosolic PLA 2 , and arachidonic acid.…”
Section: Stimulation Of Protein Synthesis By Exogenous Pld-mentioning
confidence: 99%
“…Oral administration of selected β‐adrenergic agonists (β‐AA) to rodents and livestock increases skeletal muscle mass and diminishes body fat depots (1–5). Likewise, β‐AA increase protein accumulation in cultured myotubes (6, 7) and depress fat accumulation in adipose cells in culture (8). These β‐AA effects can be reversed with the β‐antagonist propranolol (6, 8).…”
mentioning
confidence: 99%
“…Ractopamine [a β‐AA] and the cAMP analog dibutyryl‐cAMP increase protein synthesis in L 6 myoblasts (7). Both dibutyrlyl‐cAMP and forskolin appeared to increase mitogen‐activated protein kinase (MAPK) activity in L 6 myoblasts (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation